A summary of 2-, 3-MCPD esters and glycidyl ester occurrence during frying and baking processes - Goh, Kok Ming; Wong, Yu Hua; Tan, Chin Ping; Nyam, Kar Lin (Elsevier, 2021)
Monochloropropanediol (MCPD) esters and glycidyl esters (GE) are the process contaminants found in frying and baking, except the refining process. The free form MCPD and glycidol are released from their parent esters via lipase hydrolysis while they are carcinogen and genotoxic carcinogen, respectively. MCPD esters and GE are formed endogenously during vegetable oil refining process. Then, their concentration were experimented during subsequent food processing methods, especially frying and baking. This review discussed the occurrence of 2-, 3-MCPD esters and GE during frying and baking processes. Process temperature, process duration, presence of precursors, and their combined effects are highly related to MCPD esters and GE formations. An elevated temperature and processing time can increase the formation of these contaminants until an optimum rate and then followed by the decomposition. Also, other factors such as the presence of chloride ions, moisture, and partial acylglycerol can further facilitate MCPD esters and/or GE formation.